Etika Profesi Hukum dan Dampak Perkembangan Teknologi dalam Praktik Hukum di Indonesia - Endah Ratnawati; Toto Hartono; Masharin; Ida Muidah; Eko Purwanto; Iyus YL Tobing (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The enactment of Law Number 27 of 2022 on Personal Data Protection (PDP Law) marks a significant milestone in safeguarding individual human rights in the digital sphere in Indonesia. This law responds to the urgent need for a comprehensive and unified regulatory framework to replace the previously fragmented sectoral approach that lacked standardization and legal certainty. The PDP Law establishes clear principles for data processing, defines the rights of data subjects, imposes obligations on data controllers and processors, and outlines systematic mechanisms for supervision and law enforcement. This legal framework provides legal certainty not only for individuals as data owners but also for institutions managing personal data, emphasizing transparency, accountability, and data security. However, the implementation of the PDP Law still faces several challenges, including the formation of an independent supervisory authority, institutional readiness, and the public’s limited awareness of data protection rights. Therefore, synergy among the government, private sector, and civil society is essential to ensure effective enforcement. The PDP Law is not merely a normative instrument but also reflects the state’s commitment to upholding citizens' privacy rights as part of broader human rights protection in the digital era.